Suku Bunga Rill dan Keadilan Sosial: Dalam Konteks Ketimpangan Distribusi Pendapatan Pada Negara Berkembang - Tissa Asna Yenti; Doni Satria (Media Riset Ekonomi Pembangunan (MedREP), 2024)
Social justice is a matter of equality of opportunity that aims to establish a fair relationship between individuals and society. Interest is one factor that has an impact on social justice. The effect of interest on social justice is analyzed in the context of income distribution inequality. Income distribution inequality in developing countries tends to be large, indicating the high inequality that occurs. This study aims to analyze the impact of real interest rates on income distribution inequality in 64 developing countries in 2010-2019. Based on the type of data and the form of equation, this study uses Dynamic Panel Data analysis method with Generalized Method of Moment approach. This research is analyzed using System General Method of Moment (SYS GMM) two step estimator. The results show that real interest rates affect income distribution inequality. A low real interest rate will increase income distribution inequality. This is because high-income households earn most of their income from assets that are more vulnerable to interest rates than wages.